Religia w służbie polityki. Mistyka syjonizmu religijnego - Ochman, Jerzy (Studia Europaea Gnesnensia, 2016)
The aim of this article is to present the contribution of Religious Zionism to the strategy and ideology of Zionism. This contribution consisted in conferring a halo of sanctity upon Zionism, nation, state and the territory of Palestine, by means of quotes from the Torah, Jewish prophets, poets and mystics. Thanks to the efforts of Religious Zionists, Zionism as a whole gained its nationalist-religious specificity and later imparted these traits to the state Israel.